Intranasal administration of neuropeptide Y in man: systemic absorption and functional effects. - Lacroix, J. S. (1996)
1. Exogenous neuropeptide Y (NPY, 10 nmol, 50 nmol and 100 nmol) and its vehicle (NaCl 0.9%) were administered in a double blind, randomized and controlled manner by intranasal spray in 7 healthy volunteers. Variations of plasma NPY concentration over time were measured during 120 min. Forty min after the administration of 50 nmol and 100 nmol of exogenous NPY, plasma NPY increased from 5.5 +/- 1.1 pM to 9.8 +/- 2.3 pM (P < 0.05) and from 9.06 +/- 5.1 pM to 20.8 +/- 6.16 pM (P < 0.001), respectively. There was no significant modification of the mean arterial blood pressure and no subjective discomfort was reported. 2. Nasal airway resistance (NAR) was measured by anterior rhinomanometry and was reduced by 25 +/- 3% and 32 +/- 5% after the spray of 50 nmol and 100 nmol, respectively, for about 90 min. 3. Double-blind, randomized, placebo-controlled and 3-way crossover design experiments were performed in 8 healthy volunteers to evaluate the influence of intranasal pretreatment with NPY (20 nmol) and the mixed alpha 1/alpha 2-adrenoceptor agonist oxymetazoline (20 nmol) on the functional effects of subsequent local irritation evoked by capsaicin (3.3 x 10(-4) mol). Subjective evaluation of NAR and local intensity of discomfort were evaluated by means of a visual analogue scale. Nasal secretions were collected and objective NAR was recorded by rhinomanometry. 4. Subjective NAR, nasal secretions and rhinomanometry recordings were not modified by intranasal application of saline, NPY or oxymetazoline. Subjective nasal obstruction, local discomfort, nasal secretions and NAR increase evoked by capsaicin were markedly reduced by NPY pretreatment (P < 0.05) when compared to saline or oxymetazoline. 5. It is concluded that intranasal application of exogenous NPY has very low systemic absorption but induced long lasting nasal vasoconstriction without cardiovascular effects. Pretreatment of the nasal mucosa with exogenous NPY reduces both secretagogue and vasodilator responses to subsequent application of capsaicin.